NOTIFICATION OF SUSPICION: PROBLEMS OF PROCEEDING DECISION ADOPTION - Расторгуєв, Олександр Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: to investigate the defects of the Institute's legal regulation of notification of suspicion in the context of its practical implementation and to put forward proposals for their elimination. Research methodology: in the work the dialectical method of cognition, general scientific and special methods was used. Findings: proposals were made on protecting the rights of individuals from the indictment on the part of the prosecution when making a procedural decision to report suspicion. Discussion: search for ways to improve criminal procedural legislation in terms of ensuring the right of a person to be protected at the stage of pre-trial investigation. With the adoption in 2012 of the Criminal Procedural Code of Ukraine, despite the numerous changes that have been made to its further practical application, it includes defects: namely, regulatory defects of systemic, structural and logical-linguistic nature. Lack of a clear and unambiguous understanding of the «notice of suspicion» institution is one of the problems arising from the aforementioned defects, which leads to a variability in the interpretation of the relevant rules by the court, prosecution and defense parties, and the ambiguity of their practical implementation. The purpose of the scientific article is to investigate the defects of the legal regulation of the «notice of suspicion» institution in the context of its practical implementation and to put forward proposals for their elimination. The causes of the violation of the person's right to protection are the absence of clear criteria for determining the moment of the mandatory adoption of a procedural decision relating to the implementation of procedural rules as a result of delay in making such a decision on the basis of subjective evaluation criteria and accusatory bias of the prosecution party. Taking into account the above, it is proposed: 1) to establish clear criteria for determining the time of mandatory application of the «notice of suspicion» institution – delivery of a notice of suspicion and providing the person with the procedural statuse of the suspect; 2) to introduce the concept of «special witness», the volume of its procedural rights will be approximated to the procedural rights of the suspect; 3) provide the witness with so-called «active» procedural rights, namely, the right to file a petition for the recognition as a suspect and the right to appeal a procedural decision made on the basis of the petition consideration, balancing the subjective evaluation criteria of the prosecution and defense parties, until the moment, the occurrence of which gives grounds for the presentation of a person's notice of suspicion.